Group support psychotherapy for depression treatment in people with HIV/AIDS in northern Uganda: a single-centre randomised controlled trial. Issue 5 (May 2015) - Nakimuli-Mpungu, Etheldreda; Wamala, Kizito; Okello, James; Alderman, Stephen; Odokonyero, Raymond; Mojtabai, Ramin; Mills, Edward J; Kanters, Steve; Nachega, Jean B; Musisi, Seggane
Summary: Background: Group support psychotherapy (GSP) is a culturally sensitive intervention that aims to treat depression by enhancing social support, teaching coping skills, and income-generating skills. We compared GSP with group HIV education (GHE) for treatment of depression in people with HIV in Uganda. Methods: In this open-label randomised controlled trial, we included men and women with HIV, aged 19 years or older, who met the Mini International Neuropsychiatric Interview criteria for major depression from an urban HIV care centre in Kitgum district, northern Uganda. Participants were randomly assigned to receive eight weekly sessions of either GSP or GHE. Randomisation was achieved by urn (men and women separately picked a paper containing the intervention allocation from a basket; ratio 1:1), and the intervention sessions were given to gender-specific groups. Participants were followed up immediately after the intervention and 6 months after the end of treatment. The primary outcomes were change in depressive symptom scores (measured with the Self-Reporting Questionnaire) and in function scores (measured with a locally developed method), analysed by intention to treat using cluster-adjusted t tests and permutation tests. This trial is registered with The Pan African Clinical Trials Registry, number PACTR201402000742370. Findings: Between Jan 6, and Jan 20, 2014, we assessed 150 individuals, of whom 109 were randomly assigned to receive eight weekly sessions of either GSP (n=57) or GHE (n=52). Change in mean depression scores immediately after intervention did not differ between groups (mean difference −0·19, 95% CI −1·77 to 1·39, p=0·78). Mean function scores did not differ between groups either (0·24, −0·41 to 0·88; p=0·41). At 6 months after end of treatment, participants in the GSP group had lower mean depression scores than did those in the GHE group (−2·50, −3·98 to 1·02, p value=0·005), and higher function scores (0·74, −0·17 to 1·65, p=0·09) than did participants in the GHE group. No adverse events were reported. Interpretation: The benefits of existing HIV educational interventions in HIV care services could be improved by the addition of GSP content. Potential benefits of the integration of GSP into existing HIV interventions, such as adherence counselling or group HIV educational programmes, should be addressed in future studies. Funding: Grand Challenges Canada.